Pertumbuhan Ideologi Pendidikan di Era Reformasi (Kajian Terhadap Ideologi Pendidikan di Kuttab Al Fatih Purwokerto) - Fahri Hidayat (Universitas Alma Ata, 2017)
AbstrackThe momentum of reform opened the space for the development of various schools of thought and ideology in the public sphere. This is evidenced by, among other things, the emergence of religious education institutions established on the basis of ideology. That is, the discourse on ideology not only develops in discourse space, but has metamorphosed into a real movement in the social sphere. This paper examines the ideological orientation of kuttab Al Fatih Purwokerto, an elementary education institution that wishes to bring back the past to the future by taking the format and form of educational institution from a source claimed to be the original source of early Islamic education.Keyword: education ideology, kuttab al fatih, Islamic education